Awareness on Energy Efficient Products as Prediction on Intention to Subscribe to and Purchase Energy Efficient Services and Products - Mohd Radzi H.; Ghazali F.; Mohd Shokri N.; Aris H. (Springer Science and Business Media Deutschland GmbH, 2023)
Energy efficiency; Energy utilization; Forecasting; Purchasing; Surveys; Consumer attitudes; EE product; Energy efficient; Energy-efficient products; Environmental concerns; High energy consumption; Malaysia; Online surveys; Public awareness; Social media; Sales